Pore pressure evolution and fluid flow during visco‐elastic single‐layer buckle folding. Issue 2 (21st May 2015) - Eckert, A.; Liu, X.; Connolly, P.
Abstract: Pore pressure and fluid flow during the deformational history of geologic structures are directly influenced by tectonic deformation events. In this contribution, 2D plane strain finite element analysis is used to study the influence of different permeability distributions on the pore pressure field and associated flow regimes during the evolution of visco‐elastic single‐layer buckle folds. The buckling‐induced fluid flow regimes indicate that flow directions and, to a lesser degree, their magnitudes vary significantly throughout the deformation and as a function of the stratigraphic permeability distribution. The modelling results suggest that the volumetric strain and the permeability distribution significantly affect the resulting flow regime at different stages of fold development. For homogeneous permeability models ( k  > 10 −21  m 2 ), low strain results in a mostly pervasive fluid flow regime and is in agreement with previous studies. For larger strain conditions, fluid focusing occurs in the buckling layer towards the top of the fold hinge. For low permeabilities (<10 −21  m 2 ), local focused flow regimes inside the buckling layer emerge throughout the deformation history. For models featuring a low‐permeability layer embedded in a high‐permeability matrix or sandwiched between high‐permeability layers, focused flow regimes inside the folded layer result throughout the deformation history, but with significant differences in the flow vectors of the surrounding layers. Fluid flow vectors induced by the fold can result in different, even reversed, directions depending on the amount of strain. In summary, fluid flow regimes during single‐layer buckling can change from pervasive to focused and fluid flow vectors can be opposite at different strain levels, that is the flow vectors change significantly through time. Thus, a complete understanding of fluid flow regimes associated with single‐layer buckle folds requires consideration of the complete deformation history of the fold.